2017
DOI: 10.1016/j.jvoice.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Somatotype and Body Composition of Normal and Dysphonic Adult Speakers

Abstract: The findings suggested no significant differences in the somatotype and body composition variables, between normal and dysphonic speakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…8 However, several other authors [9][10][11] failed to demonstrate any correlation between body characteristics and voice. Franco et al 12 examined somatotype and body composition differences among dysphonic and nondysphonic patients in 72 adults and found no significant difference between the dysphonic group (n ¼ 32) and controls (n ¼ 40).…”
Section: Introductionmentioning
confidence: 99%
“…8 However, several other authors [9][10][11] failed to demonstrate any correlation between body characteristics and voice. Franco et al 12 examined somatotype and body composition differences among dysphonic and nondysphonic patients in 72 adults and found no significant difference between the dysphonic group (n ¼ 32) and controls (n ¼ 40).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are compatible with other studies that also reported no significant association between obesity, BMI, fat content, and voice quality (or any objective acoustic and aerodynamic measures). 16,[26][27][28][29][30] However, because almost our entire study sample was overweight or obese (ie, 95%), the range of BMI scores may be insufficient to reveal an association with having a current voice disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to establish the prevalence of current voice disorders and associated risk factors in patients with OSA. Potential risks included demographic factors, medical comorbidities, body mass index (BMI), [24][25][26][27][28][29][30] severity measures of OSA, snoring, daytime sleepiness, as well as duration and consistency of PAP therapy. The effect of a voice disorder on selected quality of life indicators was also assessed.…”
Section: Introductionmentioning
confidence: 99%
“…For clinical application, we believe that the imbalance of the phonatory system in obese individuals not only causes complaints related to phonatory effort, but also a reduction in movement precision due to an endocrine reaction, 8 9 and changes in phonatory patterns 6 (with the exception of acoustic voice measurements independent from the vocal tract 17 ) and in the focus of resonance. These deposits represent physical and structural limitations on voice rehabilitation, with a reduction in BMI as a conditional factor for therapeutic improvement, although the minimum weight loss required for fat reduction in the pharyngeal region is yet unknown.…”
Section: Discussionmentioning
confidence: 99%